Updated Species Check-list of the Indonesian Stingless Bees (Hymenoptera, Apidae, Apinae, Meliponini) - Manap Trianto; Tuty Arisuryanti; Hari Purwanto; Rosichon Ubaidillah (Journal of Tropical Biodiversity and Biotechnology, 2023)
A catalog provides an index to previous studies in taxonomy, behavioral research, and pollination ecology, thus consolidating the existing knowledge in an accessible format. In this study, we explore the annotated catalog and bibliography of the Indonesian meliponini stingless bees (Hymenoptera, Apidae, Apinae, Meliponini). The catalog format is arranged based on Rasmussen (2008). All available literature was reviewed for compiling this catalog and bibliography. References to a Meliponini genus only were not included in the list of references. Cited references must have used a trackable specific epithet to have been included. In total, Indonesia has 52 recorded stingless bee species across the Indonesian archipelagoes of Sumatera (27 species), Java (13 species), Nusa Tenggara (1 species), Kalimantan (34 species), Sulawesi (8 species), Bali (1 species), Maluku (4 species), and Papua (12 species). After the data was updated, there was an increase in the number of stingless bee species in Indonesia, namely 46 species (before update) to 52 species (after update). An up-to-date, comprehensive taxonomic and biological catalog is fundamental to any comparative evolutionary, ecological, and behavioral research on any group of organisms.